2015
DOI: 10.1053/j.ajkd.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and All-Cause Mortality in Maintenance Hemodialysis Patients

Abstract: Background Cognitive impairment is common in hemodialysis patients and associated with significant morbidity. Limited information exists on whether cognitive impairment is associated with survival, and whether type of cognitive impairment is important. Study Design Longitudinal cohort. Setting & Participants Cognitive function was assessed at baseline and yearly using a comprehensive battery of cognitive tests in 292 prevalent hemodialysis patients. Predictor Using principal component analysis, individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 21 publications
7
83
2
3
Order By: Relevance
“…Among older patients on hemodialysis, dementia likely exists on a spectrum, influenced by both vascular processes as well as the Alzheimer's disease pathology, although the former process is likely more common (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Among older patients on hemodialysis, dementia likely exists on a spectrum, influenced by both vascular processes as well as the Alzheimer's disease pathology, although the former process is likely more common (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of previous studies on sex differences between cognitive function and mortality have been inconsistent 5, 15, 25. Perna et al showed that the association between low COGTEL (Cognitive Telephone Screening Instrument) total scores and all‐cause mortality was much stronger among men than in women 15.…”
Section: Discussionmentioning
confidence: 99%
“…Inicialmente suele ser una condición asintomática y el diagnóstico puede ser sugerido por la asociación de manifestaciones inespecíficas por parte del paciente, como fatiga, pérdida de peso, picazón, hipertensión, hemólisis, poliuria entre otras. En la fase final, se llegan a observar anomalías de laboratorio y alteraciones clínicas importantes, preparando al paciente para el tratamiento de sustitución renal, diálisis o trasplante (Drew et al, 2015). En muchos sujetos con IRC, ya son conocidas enfermedades renales previas u otras condiciones clínicas subyacentes; y en un número pequeño, la causa es desconocida.…”
Section: Introductionunclassified
“…Estos trastornos cognitivos que cursan en dirección al deterioro cognitivo en los pacientes con hemodiálisis y diálisis peritoneal, es una condición aún poco reconocida como una carga importante de salud pública (Wei et al, 2014). Estos déficits cognitivos se asocian con problemas en los sistemas de memoria, el lenguaje y la función ejecutiva (Davey, Elias, Robbins, Seliger, & Dore, 2013), siendo esta última, el proceso neurocognitivo más comprometido por la insuficiencia renal (Drew et al, 2015).…”
Section: Introductionunclassified
See 1 more Smart Citation